2021
DOI: 10.1177/2158244020988709
|View full text |Cite
|
Sign up to set email alerts
|

Travelers’ Attitudes Toward Mobile Application–Based Public Transport Services in Lahore

Abstract: Many cities in developing countries are facing challenges of providing quality public transport facilities to the public. The demand-responsive transport (DRT) initiatives in some cities have helped in providing transportation alternatives to the travelers, and in filling the gap between demand and supply. Recently introduced DRT initiatives in Lahore included the mobile app-based Airlift and Swvl bus services. This article is aimed at evaluating the travelers’ attitudes toward mobile application (app)–based D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Research in Cambodia, Spanish, and Israel show that transport operators should focus on quality, convenience, and availability while keeping fares low to attract more passengers. Furthermore, public transport fares are also an issue in increasing passenger demand and loyalty [38]. This is in contrast to the condition of Trans Koetaradja buses in Banda Aceh [28], which have free fares since they started operating in 2016.…”
Section: Regression Test Resultsmentioning
confidence: 99%
“…Research in Cambodia, Spanish, and Israel show that transport operators should focus on quality, convenience, and availability while keeping fares low to attract more passengers. Furthermore, public transport fares are also an issue in increasing passenger demand and loyalty [38]. This is in contrast to the condition of Trans Koetaradja buses in Banda Aceh [28], which have free fares since they started operating in 2016.…”
Section: Regression Test Resultsmentioning
confidence: 99%
“…Another reflection concerns the methodology followed in the MENA and SA regions' transportation research; it tends to be more descriptive and limited conclusions are found based on empirical modeling results apart from a few exceptions (Soltanzadeh and Masoumi, 2014;Etminani-Ghasrodashti and Ardeshiri, 2016;Soltani and Shams, 2017;Etminani-Ghasrodashti and Hamidi, 2019;Masoumi, 2020Masoumi, , 2021Masoumi, , 2022Mehriar et al, 2020;Javid et al, 2021;Masoumi et al, 2021). The spatial data availability and analysis remains a challenge for most of the cities in the MENA and SA regions basically due to non-availability of updated information in a single repository and also hesitancy to share the information by the governing authorities.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a number of researchers have studied the urban sprawl impact on travel demand and choices in Dhaka (Nasrin et al, 2015), Chennai (Srinivasan et al, 2007a,b), Rajkot (Munshi, 2016), in all of India (Ahmad and de Oliveira, 2016), in Kathmandu (Bajracharya et al, 2020), Kabul (Kakar and Prasad, 2020), Lahore (Kamran et al, 2016;Shakeel and Jahanzaib, 2019) and Sri Lanka (Ranasinghe et al, 2015). Very few studies have evaluated the influence of people's attitudes (Javid, 2017a,b;Javid et al, 2021;Mehriar et al, 2021;Masoumi et al, 2022).…”
Section: The Determinants Of Mobility Attitudes and Mode Choicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing demand for a ride hailing application includes taxis to commute to workplaces, and home shopping, food and goods delivery [2]. The most popular transportation mobile services in the United States (US) and Europe are Uber, Lyft, Sidecar, and Carpool [3]. Meanwhile in Asia, three ride hailing applications-Didichuxing, Grab, and Go-Jek-have been listed in the top 10 Asia unicorns with the highest value and remarkable influence to people's lives.…”
Section: Introductionmentioning
confidence: 99%